Analisis Kualitatif Nilai Ekspor Migas Indonesia Dan Kepemilikan Blok Migas Oleh Perusahaan Asing Di Indonesia - Prima Gandhi (Departemen Ekonomi Sumberdaya dan Lingkungan, Fakultas Ekonomi dan Manajemen, Institut Pertanian Bogor, 2014)
The post conference of Time Life Corp in Geneva and the enactment of the Foreign Investment Act of 1967, foreign corporations began to exploit oil and gas in Indonesia. At first, the foreign corporation only managed the upstream oil and gas business. However, the oil and gas Act number 22 of 2001 made the foreign corporations do the business in the downstream sector. Data from the Ministry of Energy and Mineral showed that there was 69.9 percent of foreign domination in the Indonesian oil and gas industry. Other data showed that the value of exports of oil and gas in Indonesia decreased by the end of July 2013. The existence of these two phenomena of economic resources made the author try to examine the relation between the ownership of oil and gas blocks by foreign companies and the level of oil and gas export value in Indonesia using qualitative methods with critical paradigm. As a result, the number of oil and gas companies in Indonesia was influenced by the attitudes and government regulations, the state of technology and state of the Indonesian economy. The low value of oil and gas exports was as the result of exporting crude oil price with lower pricecompared to that of processed oil. The existence and the number of foreign oil companies influenced the level of oil and gas export value of Indonesia. The more dominated growing number of foreign companies in Indonesia, the less export value of the Indonesian oil and gas would be.